IMPLEMENTASI PENGELOLAAN ARSIP DALAM MENDUKUNG EFEKTIVITAS OPERASIONAL DI PT KEPSINDO INDRA UTAMA - Anggelita Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of records management in supporting operational effectiveness at PT Kepsindo Indra Utama. Records, as a source of strategic information, play an important role in accelerating administrative processes, improving data accuracy, and supporting managerial decision-making. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that archive management at PT Kepsindo Indra Utama has implemented archival principles such as classification, storage, and maintenance, but there are still obstacles in terms of archive digitization and limited human resources. The implementation of a more structured and information technology-based archive management system has proven to improve operational efficiency, minimize the risk of data loss, and accelerate administrative services. Thus, optimal archive management is a key factor in supporting smooth work processes and operational effectiveness of the company.